218k views
1 vote
Solve each system by substitution. y=3x+4 y=4x+7

User Comet
by
4.3k points

1 Answer

6 votes

We need to solve the following system by substituition:


\begin{cases}y=3x+4 \\ y=4x+7\end{cases}

To solve by substituition means that we need to isolate one variable in one of the equations and replace one expression with the other. This is done below:


\begin{gathered} (3x+4)=4x+7 \\ 3x+4=4x+7 \\ 3x-4x=7-4 \\ -x=3 \\ x=-3 \end{gathered}

Then we need to replace the value of "x" in any of the two equations.


\begin{gathered} y=3\cdot(-3)+4 \\ y=-9+4 \\ y=-5 \end{gathered}

The solution is (-3,-5).

User Saleh Feek
by
4.6k points